Effect of synthesis parameters on structural and morphological properties of nanocrystalline bismuth phosphorus oxide materials - Khairi Osman, Hartini (2013)
Bismuth phosphorus oxide (BPO) has attracted much attention due to its various applications such as catalysts, photocatalysts, ionic conductors, and metal ion sensors. This material is usually produced via solid state reaction, hydrothermal synthesis, and ball milling which are associated with long reaction time, high synthesis temperature, and microsized products. Thus, an attempt was carried out in this research to synthesize nanocrystalline BPO using a relatively simple hot injection method at low reaction temperature. Bismuth acetate and calcium phosphide were used as precursors of bismuth and phosphorus, respectively. Phosphorus precursor reacted with 4 M hydrochloric acid (HCl) to generate phosphine (PH3) gas which later reacted with bismuth precursor in a mixture of 1-octadecene (ODE) and myristic acid (MA). Several parameters in synthesis condition including reaction temperature, type of reaction solvent, ratio of stabilizer (MA) to reaction solvent (ODE), amount of reaction solvent, reaction time, and ageing time were investigated. X-ray diffraction (XRD) results suggested that single phase BPO material with high crystallinity was obtained at reaction temperature 180°C with reaction time of 30 minutes and ratio of MA:ODE of 1:90. The XRD pattern of this material was best fitted with that of reported Bi3.69P0.31O6.31 (PDF 2010:43-0455), implying formation of face centered cubic (FCC) phase with lattice parameter a = 0.5416 nm. This FCC phase was in good agreement with transmission electron microscopy (TEM) analysis with average lattice fringes spacing of 0.337 nm. As evidenced, TEM and XRD results showed that particle size of the materials were in range of 10 to 20 nm. These materials are interesting as they have an ordered lamellar structure with both large meso and macro pores, indicating the formation of porous structure between the layers of BPO materials. In conclusion, nanocrystalline BPO was successfully synthesized via hot injection method for the first time.